Guatemala Economic DNA : Harnessing Growth with a Special Focus on Jobs - World Bank Group (Guatemala, 2014)
This is the first edition of the of the Guatemala Economic DNA (Diagnostic for National Action) with a focus section on job creation. The report highlights the important achievements of Guatemala on the macroeconomic stability front. It also argues that these achievements will need to be secured and makes the case for an increased focus on accelerating economic growth. For example, this edition highlights that in 2013 the country's economic activity expanded by 3.7 percent in 2013, and is projected to grow around 3.6 percent in the near-term, in line with the growth of Central American economies but below the growth rate in emerging markets. Meanwhile, inflation has been managed and the authorities deserve to be recognized for their commitment to maintain macroeconomic stability. Guatemala's economy has recovered at a modest but consistent pace since the global financial crisis of 2008-09. Guatemala's macroeconomic resilience is due to prudent macroeconomic policies and a more diversified economy in comparison to other Central American countries, which has helped cushion the impact of shocks. Accelerating growth can substantially reduce poverty in Guatemala, but this will require improvements in economy-wide productivity. Public investment is essential to achieving Guatemala's development goals, yet it remains tightly constrained by a lack of resources, and the government continues to collect the lowest share of public revenues in the world relative to the size of its economy. This report, underscores the extent to which structural constraints on enterprise development slow hiring rates, discourage technology transfer, and promote informality. Several cross-cutting factors are also closely correlated with job creation in Guatemala, including financial depth, exposure to corruption, and informality. Strengthening the rule of law and streamlining regulatory systems will be essential to facilitating firm growth, fostering greater competitiveness, and boosting the returns to both labor and capital.